(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The subject of this paper is new geological and stratigraphical data regarding the Paleozoic in the Sarrabus area (Southeastern Sardinia). More particularly Tremadocian (Lower Ordovician) acritarchs have been found in samples taken for microfossils research from the weakly metamorphosed terrigenous sediments of the San Vito Sandstone. Until recently only acritarchs from the Middle and Upper Cambrian has been found in the San Vito Sandstone. This new finding provides a more precise dating of the San Vito Sandstone, a more exact correlation between this Sarrabus formation and analogous formations with acritarchs in Central- Eastern Sardinia and also further confirmation of the Intraordovician age of the Sarrabese Phase and of the corresponding Sardic Phase of Iglesiente-Sulcis area (Southwestern Sardinia).